GE_GERICHTE C/11667/2008 vom 2. November 2012 - GE Cour de justice (2012)
TORT MORAL; CONSENTEMENT DU LÉSÉ; PATIENT; EXPERTISE MÉDICALE; RESPONSABILITÉ DE DROIT PRIVÉ | CO.394.1; CO.398.2; CC.8; CO.47; CO.49; CO.97